Engineering Asset Management 2016 Proceedings of the 11th World Congress on Engineering Asset Management - Zuo, Ming J.; Ma, Lin; Mathew, Joseph; Huang, Hong-Zhong (Lecture Notes in Mechanical Engineering,, 2018)
These proceedings gather selected peer-reviewed papers from the 11th World Congress on Engineering Asset Management (WCEAM), which was held in Jiuzhaigou, China, on 25-28 July, 2016. These proceedings cover a wide range of topics in engineering asset management, including: ·         strategic asset management; ·         condition monitoring and diagnostics; ·         integrated intelligent maintenance; ·         sensors and devices; ·         information quality and management; ·         sustainability in asset management; ·         asset performance and knowledge management; ·         data mining and AI techniques in asset management; ·         engineering standards; and ·         education in engineering asset management. The breadth and depth of these state-of-the-art, comprehensive proceedings make them an excellent resource for asset management practitioners, researchers and academics, as well as undergraduate and postgraduate students.